2019 IEEE International Conference on Artificial Intelligence Testing (AITest) 2019
DOI: 10.1109/aitest.2019.000-6
|View full text |Cite
|
Sign up to set email alerts
|

Input Prioritization for Testing Neural Networks

Abstract: Deep neural networks (DNNs) are increasingly being adopted for sensing and control functions in a variety of safety and mission-critical systems such as self-driving cars, autonomous air vehicles, medical diagnostics and industrial robotics. Failures of such systems can lead to loss of life or property, which necessitates stringent verification and validation for providing high assurance. Though formal verification approaches are being investigated, testing remains the primary technique for assessing the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…By removing such corner cases we expect to get a less discriminative test set, which is less effective in assessing the quality of the model under test. This approach has previously been used for a similar task by Jahangirova & Tonella [22] and for test input prioritisation by Byun et al [13]. In our experiment, for classification systems we build a weak test set by keeping only the test inputs that are predicted with a confidence equal to 1, where confidence is measured as the highest softmax output value.…”
Section: Rq3 [Comparison Withmentioning
confidence: 99%
“…By removing such corner cases we expect to get a less discriminative test set, which is less effective in assessing the quality of the model under test. This approach has previously been used for a similar task by Jahangirova & Tonella [22] and for test input prioritisation by Byun et al [13]. In our experiment, for classification systems we build a weak test set by keeping only the test inputs that are predicted with a confidence equal to 1, where confidence is measured as the highest softmax output value.…”
Section: Rq3 [Comparison Withmentioning
confidence: 99%
“…DeepCT [50] proposes a combinatorial testing approach, while DeepCover [69] adapts MC/DC from traditional software testing and defines adequacy criteria that investigate the changes of successive pairs of layers. Recent research also proposes testing criteria and techniques driven by symbolic execution [31], coverage guided fuzzing [56,76] and metamorphic transformations [72], while other research explores test prioritization [16] and fault localisation [24].…”
Section: Related Workmentioning
confidence: 99%
“…These two aspects lead to high test generation costs. Byun et al [148] used DNN metrics like cross entropy, surprisal, and Bayesian uncertainty to prioritise test inputs and experimentally showed that these are good indicators of inputs that expose unacceptable behaviours, which are also useful for retraining.…”
Section: Test Prioritisation and Reductionmentioning
confidence: 99%